Visibilidade importa? Publicações ex ante e comportamento decisório do Supremo Tribunal Federal - (:unkn) unknown (Universidade Federal do Pampa, 2024)
This article, still under development, follows an approach to analyze the decision-making behavior of constitutional courts and their relationship with the public, focusing on the case of the Brazilian Supreme Federal Court (STF). Through statistical analyses and data mining techniques, it was examined whether the outcomes of constitutional review decisions would be affected by increased visibility provided by previous media coverage of cases. Does the court decide differently when subjected to greater salience? Keeping other variables constant, the occurrence of media publication would double the chances of the Adin (Direct Action of Unconstitutionality) outcome being upheld. Based on the literature on cases similar to the Brazilian scenario and according to the theory of public reinforcement, a positive relationship was also found between higher visibility and the probability of counter-majoritarian outcomes. However, based on the preliminary results, in isolation, salience did not prove to be a relevant factor in explaining the variation in decision outcomes, as the model did not present statistical significance. The model, including all proposed independent variables, did not demonstrate high explanatory capacity, being limited to explaining approximately 24% of the variation in constitutional review decision outcomes. While it is not possible from the data analysis to assert that greater salience has a strong relationship with the STF’s decision-making behavior, it is undeniable that decision-making depends on the coexistence of other factors related to the political environment and the nature of the issue. If the presence of previous publications, even with all controls applied, showed a positive relationship, it indicates that the media, as a factor influencing judicial behavior, deserves more attention in the research agenda on judicial institutions.
Does visibility matter? Ex ante publications and decision-making behavior of the Brazilian Supreme Court
Keywords: Comportamento organizacional; Democracia; Brasil. Supremo Tribunal Federal; Modificação do comportamento; Avaliação do comportamento; Organizational behavior; Democracy; CNPQ::CIENCIAS SOCIAIS APLICADAS